Unemployment and Structural Unemployment in the Baltics - Ebeke, Christian; Everaert, Greetje (Washington, D.C. : International Monetary Fund, 2014)
While the unemployment rate in the Baltics has fallen sharply from its crisis-peaks, it remains close to double digits. This paper estimates the structural component of the jobless rate in the three Baltic countries and analyzes its causes. Our main findings are that the current still elevated levels of unemployment mostly reflect structural factors. We then turn to why structural unemployment is so high. This paper points to skill mismatches, high tax wedges, and unemployment and inactivity traps as potential causes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet